Effectiveness of Ethical Leadership on Job Satisfaction: Mediating Role of Organizational Citizenship Behavior - Nawaz, Amjad; Aihua, Gu; Khan, Muhammad Farhan (Pakistan Journal of Humanities and Social Sciences, 2022)
Recently, ethical leadership has opened innovative thought pathways that have attracted global human resource managers’ attention because of their efficacy and positive impact on organizational citizenship behavior. This research demonstrates the magnitude of employees’ job satisfaction impacts performance motivated by ethical leadership and organizational citizenship behavior. This study aims to determine the influence of ethical leadership on employees’ job satisfaction and OCB. Using a convenience sample design, data were collected from 230 employees. SmartPLS-3 software was used for data analysis. The results of this study reveal that ethical leadership has a positive impact on job satisfaction. Organizational citizenship behavior has mediated the relationship between job satisfaction and ethical leadership. The finding shows that ethical leadership has a significant impact on employees’ job satisfaction as well as a partial mediating relationship. Based on the findings, we present the theoretical and policy implications, limitations, and future studies pertinent to this research